Recitation of Moving the Body and Erecting a Tomb Cupola: The Independence of Habib Salim's Religious Criticism in the Al-Ibānah Manuscript - Abror, Muhamad; Misbachul Islam, Adib (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2024)
This research aims to examine the independence of Habib Salim bin Jindan (1906-1969) in responding to religious practices in Indonesia in the 20th Century, particularly regarding the legality of bodily movements during dhikr and the permissibility of constructing tomb structures. One religious issue of the 20th Century was the religious criticism involving two groups of Muslims: the traditionalists and the modernists. The traditionalist camp was considered more accommodating towards existing religious practices, whereas the modernist Muslims took a contrasting stance. To date, studies on this issue have primarily focused on the two critical typologies: traditionalists and modernists. Traditionalist Muslims, based on Imam Shāfi’i’s concept, categorize innovations (bid‘ah) into two types: good and bad. In contrast, modernist Muslims, following Imam Mālik’s concept, regard all forms of bid‘ah as harmful, with those who practice it destined for punishment in hell. In his work al-Ibānah fī Tārīkh al-Sunnah, Habib Salim conducts independent religious criticism, without aligning with either the traditionalist or modernist paradigms. This article is a qualitative study employing a literature review, with philological and socio-intellectual approaches relevant to the Indonesian context in the 20th century. The research uncovers several findings. First, modernist Muslims tend to be rigid and strict in responding to religious practices within society, while traditionalist Muslims are more accommodating. Second, Habib Salim, as a scholar from the traditionalist circle, was critical of certain religious practices. Third, this ḥadramī figure developed an independent theory of bid‘ah criticism, meaning he did not follow the ideological currents of either traditionalist or modernist Muslims. Fourth, this neutral stance allowed Habib Salim to adopt a more moderate perspective when addressing differences of opinion.